THE PECULIARITIES OF INTEGRATED TEACHING OF THE CATEGORY OF CASE BASED ON THE COMPARISON OF ARMENIAN AND RUSSIAN LANGUAGES (EDUCATION IN THE 21ST CENTURY, 2022)
Guided by the constructive basics of mother tongue teaching, we constantly build interdisciplinary connections around Linguistics throughout our work, as the knowledge of all disciplines, including foreign languages, is based on the knowledge of the mother tongue. While there are very few exercises on revealing interdisciplinary relationships in modern textbooks of the Armenian language, exercises on revealing the connections between foreign languages are completely missing. Through the strategy of ‘comparison’, it is necessary to give students a chance to analyze the basic relationships of the grammatical category of case in Armenian and Russian.In this way, students will make sense of their own speech, combining their school experience with their everyday life, which will greatly contribute to their interactions with foreigners.
Keywords: mother tongue; interdisciplinary connections; Linguistics; foreign languages; grammatical category